Hydrokinetic energy harnessing for river application - Wan Ismail, Ibrahim; Raja Mohd Taufika, Raja Ismail; Marina, Mohamed (UTeM, 2018)
Hydrokinetic Energy Conversion System (HECS) is the electromechanical devices that able to harness the electricity from river current, tidal stream or man-made water irrigation system. In this work, design considerations of verticalaxis hydrokinetics turbine for Pahang river have been initiated. Double multiple streamtube (DMS) algorithm in QBlade software has been used to determine the rotor performance. In this design, NACA 0015 hydrofoils, and three blade rotor configurations with 0.25m chord length has been identified. Based on simulation design, the H-Darriuse turbine able to harness 200W output power at 0.582m/s water velocity with 5.5m2 swept area.